Cardiac tamponade due to rupture of a giant coronary aneurysm over coronary fistulas: Report of an unusual case - Chavez Solsol, Jorge Francisco (2020)
Coronary artery fistulas are rare clinical entities, and their association with giant coronary aneurysms is even more unusual. Most fistulas are asymptomatic, in the other hand, aneurysms could develop symptoms depending on their diameter. We present the clinical case about a patient with chest pain and cardiac arrest, who later developed cardiac tamponade with the need for emergency surgery, due to rupture of a giant coronary aneurysm developed from confluent coronary artery fistulas from two coronary arteries to pulmonary artery.